2006
DOI: 10.1385/cbb:44:1:031
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies for Cardiovascular Gene Therapy: Regulatable Pre-Emptive Expression of Pro-Angiogenic and Antioxidant Genes

Abstract: Cardiovascular diseases are among the major targets for gene therapy. Initially, clinical experiments of gene transfer of vascular endothelial growth factor (VEGF) improved vascularization and prevented the amputation in patients with critical leg ischemia. However, the majority of trials did not provide conclusive results and therefore further preclinical studies are required. Importantly, data indicate the necessity of regulated expression of angiogenic factors, particularly VEGF, to obtain the therapeutic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…32 These studies revealed that the protection afforded by eNOS overexpression was NO dependent. Given the current interest [33][34][35] in translating gene therapy to the clinic, we sought to further clarify the protective effects of tissue-specific eNOS overexpression versus global overexpression. Using 2 distinct transgenic mice, we compared systemic versus tissue-specific (cardiomyocytespecific) eNOS overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…32 These studies revealed that the protection afforded by eNOS overexpression was NO dependent. Given the current interest [33][34][35] in translating gene therapy to the clinic, we sought to further clarify the protective effects of tissue-specific eNOS overexpression versus global overexpression. Using 2 distinct transgenic mice, we compared systemic versus tissue-specific (cardiomyocytespecific) eNOS overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic approaches that have been considered include mechanisms 1) to increase antioxidant capacity, 2) to increase NO bioavailability, and 3) to reduce ROS generation by decreasing activity of ⅐O 2 Ϫ -generating enzymes (121). Gene therapy targeting oxidant systems, such as NOS and hypoxia-inducible factor 1 (HIF-1) (122,123), are also being developed, but their use in clinical hypertension remains unclear.…”
Section: Therapeutic Potential Of Reducing Ros In Human Hypertensionmentioning
confidence: 99%
“…171,172 In fact Nox isoforms may be attractive therapeutic targets for vascular disease. [171][172][173] New peptide inhibitors that have been developed to specifically target NADPH oxidases include the 18 amino acid peptide gp91ds-tat, which interferes with Nox and subunit assembly, because nine of the amino acids mimic the region of p22phox that interacts with p47phox. 174 PR39, a naturally occurring 39 amino acid proline-and arginine-rich peptide that binds to Src homology domain 3 of p47phox also prevents association between p47phox and Nox, thereby inhibiting oxidase assembly and activation.…”
Section: Therapeutic Potential Of Ros Modulators In Hypertensionmentioning
confidence: 99%